(untitled) (Journal of the Bangladesh Agricultural University, 2026)
The experiment was conducted to determine the feed intake and body weight (BW) change of Boer cross buck supplemented with a commercial concentrate mass and combinations of commercial concentrate (CF) with duckweed (Lemna minor) at varying inclusion levels at Goat Research Farm of the Directorate of Agricultural Research (DoAR), Khajura, Banke District, under Nepal Agricultural Research Council (NARC) Nepal for 90 days (2024/25). In the experiment sixteen healthy bucks 6-7 months old with an average initial body weight 14.43 kg were randomly allocated to four dietary treatments:100% CF+ 0% duckweed (T0), 90 % CF + 10% duckweed (T₁), 80% CF + 20% duckweed (T₂), and 70% CF + 30 % duckweed (T₃), with ad libitum Napier grass provided across all groups. The results reveled that, significant (p<0.05) difference was observed in a total dry matter intake (DM, g/d) and found highest in control group T1 and lowest in treatment T2, i.e., substitution with increasing rate of duckweed reduce the total dry mater intake. However, the difference was non- significant with treatment T2 and T3. Total body weight gain, average daily body weight gain and final body weight was observed significantly (p<0.05) highest in treatment T2 and lowest in T1, whereas the difference was non -significant (p>0.05) between treatment T2 and T3. Similarly, feed conversion ratio (FCR) was observed lowest in T2 treatment compared to T1 and the difference was non-significant with treatment T2 and T3. From the results it indicated that, duckweed is a good source of protein and it can utilize up to 20% as substitution of concentrate ration during growing period of goat without compromising their growth performance. J Bangladesh Agril Univ 24(1): 45–48, 2026